An Analysis Of Metaphor In James Arthur Song’s Lyric - elia, Elia Putri Ribka; Sidabutar, Usman; Siahaan, Sahat Taruli (Kopula: Jurnal Bahasa, Sastra, dan Pendidikan, 2024)
This research discusses the analysis of metaphors contained in the lyrics of James Arthur's song on his 3rd album entitled "You" in 2019. The purpose of this study is to classify the types of metaphors and see the most dominant types of metaphors. This research was conducted using a descriptive qualitative method. The data this research underline song lyrics that contain metaphors. The song lyrics are taken from James Arthur’s YouTube account and also from the Google site obtained on March 26, 2024, at 08.00 pm. The data collection instruments used were observation and documentation. Data were obtained from 12 James Arthur songs. The author found 85 data in James' song lyrics. The types of metaphors contained in James Arthur's song lyrics are active metaphor 19 data, inactive metaphor 11 data, subjective metaphor 25 data, asymmetric metaphor 10 data, dead metaphor 11 data, and mimetic metaphor 9 data. The most dominant type is subjective metaphor, which is 25 data. Therefore, subjective metaphor is found more in 12 songs of James Arthur in his 3rd album “You” in 2019. The benefits of this research for the state and nation, especially in the field of teaching is that teachers can teach using subjective metaphors, that is teaching or interacting with students by using more feelings in the teaching and learning process.